2005
DOI: 10.1016/s0167-2991(05)80470-7
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effects in the oxidation of CO over zeolite-supported Pt nanoparticles

Abstract: Well-defined Pt-nanoparticles with an average diameter of 1 nm supported on a series of zeolite Y samples containing different monovalent (H + , Na + , K + , Rb + , and Cs + ) and divalent (Mg 2+ , Ca 2+ , Sr 2+ , and Ba 2+ ) cations have been used as model systems to investigate the effect of promotor elements in the oxidation of CO in excess oxygen. Time-resolved infrared spectroscopy measurements allowed us to study the temperatureprogrammed desorption of CO from supported Pt nanoparticles to monitor the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Therefore, the single Pd sites, isolated by Ir atoms, may inhibit the formation of unwanted H 4 eAQ products. Moreover, it can be seen that the peak for bridging CO on Pd atoms becomes slightly blue‐shifted after addition of Ir, suggesting that there is some charge transfer from Pd to Ir . As reported elsewhere, eAQ is an electrophilic reagent, and the Pd catalyst may be considered as a nucleophilic reagent in the hydrogenation reaction .…”
Section: Resultssupporting
confidence: 89%
“…Therefore, the single Pd sites, isolated by Ir atoms, may inhibit the formation of unwanted H 4 eAQ products. Moreover, it can be seen that the peak for bridging CO on Pd atoms becomes slightly blue‐shifted after addition of Ir, suggesting that there is some charge transfer from Pd to Ir . As reported elsewhere, eAQ is an electrophilic reagent, and the Pd catalyst may be considered as a nucleophilic reagent in the hydrogenation reaction .…”
Section: Resultssupporting
confidence: 89%
“…In Figures 2(a) and 2(b), the assignments of the CO absorption peaks at 2068-2050 cm -1 , 1840 cm -1 , 1708 cm -1 to linear (COL), bridging (COB) and other multiply-bonded (COMB) CO, respectively, is in accordance with literature 17,18 . The weak absorption at 1656 cm -1 (for which is corrected in the inset of Figure 2(a)) is most likely due to the presence of water 19,20 .…”
Section: Co Adsorption Atr-ir Measurementssupporting
confidence: 84%
“…Pt/SiO2 33 and Pt/Zeolites 34 . In these studies, the integrated intensity ratio of the COL/CO bridging drops significantly, suggesting an increase in the electron density on the metal atom with increasing alkalinity of the support 5,18,24,33,34 . Our results are in agreement with J. T. Miller et al, who reported a shift to lower frequency and a decrease in the linear to bridging ratio as the alkalinity of the support increases 35 .…”
Section: Co Adsorption Atr-ir Measurementsmentioning
confidence: 91%
See 2 more Smart Citations